Elite coaches views on factors contributing to excellence in orienteering - Celestino, Tadeu (2015)
In the sport of orienteering, the studies in the context of sporting excellence are still scarce. Investigations carried out to date have been focused on the isolated analysis of specific factors contributing to excellence. The aim of this study therefore was to identify factors that coaches consider most prevalent in the development and maintenance of excellence in this sport. Ten elite level Portuguese and Spanish orienteering coaches completed semi-structured interviews and data were analysed using content analysis. Results showed coaches placed great emphasis on a set of personal factors, designated as primary influencing factors, including psychological attributes, sports preparation and genetic factors. Coaches also identified environmental factors that exert a secondary influence, with particular emphasis on the family, the sociocultural aspects and peer and friendship groups. Finally, elite coaches recognized the need of interaction and interconnection between these primary and secondary influencing factors for the development and maintenance of excellence in orienteering.